2020
DOI: 10.1002/fes3.260
|View full text |Cite
|
Sign up to set email alerts
|

Maize‐based intercropping systems achieve higher productivity and profitability with lesser environmental footprint in a water‐scarce region of northwest China

Abstract: Global agriculture is facing multiple challenges to meet the food demands, optimize resource utilization, and mitigate the climate change. A field study, combined with the life cycle assessment (LCA), was conducted to select the effective and sustainable cropping systems in northwestern China. The study compared four maize‐based intercropping and corresponding monoculture systems on crop yield, evapotranspiration (ET), water use efficiency (WUE), profitability, and carbon footprint (CF). Maize/wheat intercropp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 39 publications
2
10
1
Order By: Relevance
“…The little loss of coffee yield and gain of macadamia yield (positive AYL values) in the intercropping system provided better exploitation of available resources than under monocrops (Dhima et al, 2007;Gitari et al, 2020;Machiani et al, 2018). Intercropping has been considered a practical system to alleviate drought risk under global climate change, because it had a higher yield advantage in dry conditions than that in wet ones (Sun et al, 2021;Wang et al, 2020), as corroborated by this study.…”
Section: Efficiency Of the Intercropping System In The Two Water Regimessupporting
confidence: 74%
“…The little loss of coffee yield and gain of macadamia yield (positive AYL values) in the intercropping system provided better exploitation of available resources than under monocrops (Dhima et al, 2007;Gitari et al, 2020;Machiani et al, 2018). Intercropping has been considered a practical system to alleviate drought risk under global climate change, because it had a higher yield advantage in dry conditions than that in wet ones (Sun et al, 2021;Wang et al, 2020), as corroborated by this study.…”
Section: Efficiency Of the Intercropping System In The Two Water Regimessupporting
confidence: 74%
“…The result revealed that the financial benefits of the intercropping system are higher than the sole cropping system. These results were in accord with the research studies [20][21][22] Benefit-Cost Ratio (BCR) analyses were performed for farmers operating under the intercropping and sole tomato cropping system. The result revealed that tomato-onion intercropping gave a high BCR of 2.35 as compared to sole tomato with BCR 1.88 (table 3).…”
Section: Modified Policy Analysis Matrix (Pam)supporting
confidence: 85%
“…This method is also suitable for mechanized seeding, fertilization and field management [5]. Maize and peanut strip intercropping not only improves crop yield and water and fertilizer utilization efficiency but also reduces competition for major soil nutrients, increases beneficial soil microorganism numbers and diversity, and reduces pathogenic and poisonous microorganisms, effectively improving the ecological environment of farmland [6,7] while helping to reduce carbon emissions and to increase the economic value of the ecosystem [8].…”
Section: Introductionmentioning
confidence: 99%